Val108/158Met polymorphism in the catechol-omethyl transferase (COMT) dopaminergic gene in mestizo Peruvian population and its importance in neuropsychiatric studies - Huerta, Doris (2007)
Introduction: Dopaminergic catechol-o-methyl transferase (COMT) gene has a functional polymorphism Val108/158Met that originates enzyme variants that catalyze o-methylation of active catecholamines and participates in drugs and neurotransmitters metabolism including L-dopa, norepinephrine, epinephrine and dopamine and thus may be associated to neuropsychiatric conditions. Objectives: To determine COMT gene genotypes and alleles frequencies in mestizo Peruvian population healthy subjects and its importance in neuropsychiatric genetic studies. Design: Descriptive, observational, transversal study. Setting: Alberto Guzman Barron Biochemistry and Nutrition Research Center, Faculty of Medicine, Universidad Nacional Mayor de San Marcos. Participants: One hundred and six healthy subjects, male and female volunteers with informed consent, without family relationship or mental and neurological disorders as determined by clinical assessment, all Lima residents, aged between 18 and 50 years. Interventions: Genomic DNA was extracted from buccal epithelium cells to 106 individuals seemingly healthy, previous informed consent, using standard methodology. We typed using polymerase chain reaction (PCR) of the relevant region followed by digestion with N1aIII enzyme and polyacrilamyde gel electrophoresis and silver nitrate stain. Main outcomes measures: COMT gene genotypes and alleles frequencies in mixed Peruvian population. Results: We found frequencies Met/Met genotype=0,0661, Val/Met genotype=0,5094, and Val/Val genotype=0,4245, distribution consistent with Hardy-Weinberg expectations (X2 = 3,0317, g.l.=1, p >0,05). Alleles frequencies were Val allele=0,679 and Met allele=0,321. Conclusions: Val/Met heterozygote and Val allele were significantly more common in the mixed Peruvian population. In gene-gene interaction and gene-environment Val108/158Met polymorphism must be considered in neuropsychiatric genetic studies in both mixed and native populations.